Evaluating dose delivered of a behavioral intervention for childhood obesity prevention: a secondary analysis - William J. Heerman; Evan C. Sommer; Ally Qi; Laura E. Burgess; Stephanie J. Mitchell; Lauren R. Samuels; Nina C. Martin; Shari L. Barkin (BMC Public Health, 2020)
Abstract Background Current recommendations for intensive behavioral interventions for childhood obesity treatment do not account for variable participant attendance, optimal duration of the intervention, mode of delivery (phone vs. face-to-face), or address obesity prevention among young children. A secondary analysis of an active one-year behavioral intervention for childhood obesity prevention was conducted to test how “dose delivered” was associated with body mass index z-score (BMI-Z) across 3 years of follow-up. Methods Parent-child pairs were eligible if they qualified for government assistance and spoke English or Spanish. Children were between three and 5 years old and were at risk for but not yet obese (BMI percentiles ≥50th and < 95th). The intended intervention dose was 18 h over 3-months via 12 face-to-face “intensive sessions” (90 min each) and 6.75 h over the next 9 months via 9 “maintenance phone calls” (45 min each). Ordinary least-squares multivariable regression was utilized to test for associations between dose delivered and child BMI-Z immediately after the 1-year intervention, and at 2-, and 3-year follow-up, including participants who were initially randomized to the control group as having “zero” dose. Results Among 610 parent-child pairs (intervention n = 304, control n = 306), mean child age was 4.3 (SD = 0.9) years and 51.8% were female. Mean dose delivered was 10.9 (SD = 2.5) of 12 intensive sessions and 7.7 (SD = 2.4) of 9 maintenance calls. Multivariable linear regression models indicated statistically significant associations of intensive face-to-face contacts (B = -0.011; 95% CI [− 0.021, − 0.001]; p = 0.029) and maintenance calls (B = -0.015; 95% CI [− 0.026, − 0.004]; p = 0.006) with lower BMI-Z immediately following the 1-year intervention. Their interaction was also significant (p = 0.04), such that parent-child pairs who received higher numbers of both face-to-face intensive sessions (> 6) and maintenance calls (> 8) were predicted to have lower BMI-Z. Sustained impacts were not statistically significant at 2- or 3-year follow-up. Conclusions In a behavioral intervention for childhood obesity prevention, the combination of a modest dose of face-to-face sessions (> 6 h over 3 months) with sustained maintenance calls (> 8 calls over 9 months) was associated with improved BMI-Z at 1-year for underserved preschool aged children, but sustained impacts were not statistically significant at 2 or 3 year follow-up. Clinical trial registration The trial was registered on ClinicalTrials.gov ( NCT01316653 ) on March 16, 2011, which was prior to participant enrollment.